Hukum Homoseksual Perspektif Maqashid Syariah - Siska Lis Sulistiani (Institut Agama Islam Negeri Curup, 2019)
The purpose of this study is to find out aspects of sharia maqashid or the objectives and wisdom of the rule of law related to homosexual behavior, because the purpose of law enforcement is in addition to causing deterrent effects for the culprit and awake a sense of justice for all humans. This research is a normative juridical study, which uses secondary data in the form of primary, secondary and tertiary legal sources (library data), collected through library research and analyzed qualitatively descriptive. So that the discussion can be found in accordance with the data obtained. The results of this study state that Islam exists as a religion contained in universal and humanist legal aspects, for the benefit of all beings in the world. Deviant behavior such as homosexuality is a behavior that is given harsh sanctions in Islam because for the sake of maintaining the benefit of human life, both in terms of protecting offspring (hifdz nasab), maintaining honor (hifdz irdh) and health (hifdz nafs). Sharia maqasid needs to be understood from a strict rule, especially aspects of Islamic criminal law so that Muslims can understand thoroughly the rule of law is not just believe or become a phobia.